1997
DOI: 10.1097/00005768-199701000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Family size and age at menarche in athletes

Abstract: The association between family size and age at menarche was evaluated in 370 university athletes representing seven sports, 291 white and 79 black. Age at menarche, number of children in the family (family size), and birth order were collected retrospectively by questionnaire with a follow-up interview if necessary. The effect of family size on menarche was estimated with linear regression and multiple regression. For each additional sibling in the family-age at menarche was later by 0.17 yr in white athletes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 25 publications
2
30
2
1
Order By: Relevance
“…Finally, the daughters' generation reported a range of ages at menarche that spanned only 7 years. This consecutive decrease of age at menarche may be due to better nutritional and health status (Malina et al 1997) during the rapid socio-economic transition occurring over these three generations in Taiwan.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, the daughters' generation reported a range of ages at menarche that spanned only 7 years. This consecutive decrease of age at menarche may be due to better nutritional and health status (Malina et al 1997) during the rapid socio-economic transition occurring over these three generations in Taiwan.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies identified many factors that influence age at menarche such as ethnicity, geographical location, nutrition, socio-economic conditions, family environment, exercise, and stressful life events (Brooks-Gunn and Warren 1988;Eveleth and Tanner 1990;Malina et al 1997;Pasquet et al 1999;Marrodan et al 2000;Salces et al 2001;Biro et al 2006). Since the 19th century, age at menarche has fallen sharply in most European countries (Rimpela and Rimela 1993;Liestol and Rosenberg 1995;Bodzsar and Susanne 1998;Helm and Grolund 1998;Papadimitriou et al 1999;Marrodan et al 2000;Olesen et al 2000;de Muinch Keizer and Mul 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is influenced by memory and recall bias (the shorter the recall interval, the more accurate the recall, and vice versa). Recalled ages tend to be reported as whole years, typically CA at the birthday before menarche 23 24. A detailed interview can help women recall ages more precisely.…”
Section: Assessment Of Maturity Status and Timingmentioning
confidence: 99%
“…However, it is still possible that the present results could have been affected by differences between intact and disrupted families in the number or positioning of other siblings in the family. Specifically, past research has suggested that family size and birth order may influence pubertal timing, though findings have been inconsistent (reviewed in Ma- lina, Katzmarzyk, Bonci, Ryan, & Wellens, 1997;Matchock & Susman, 2006). Accordingly, we compared (a) the birth order positions of the older and younger sisters and (b) overall family size across the two family types.…”
Section: Potential Confounding Effects Of Between-family Differences mentioning
confidence: 99%